Structure and sites of phosphorylation of 14-3-3 protein: role in coordinating signal transduction pathways. - Dubois, T; Howell, S; Amess, R; Kerai, P; Learmonth, M; Madrazo, J; Chaudhri, M; Rittinger, K; Scarabel, M; Soneji, Y; Aitken, A (1997)
The 14-3-3 family are homo- and heterodimeric proteins whose biological role has been unclear for some time, although they are now gaining acceptance as a novel type of 'adaptor' protein that modulates interactions between components of signal transduction pathways, rather than by direct activation or inhibition. It is becoming apparent that phosphorylation of the binding partner and possibly also the 14-3-3 proteins may regulate these interactions. 14-3-3 isoforms interact with a novel phosphoserine (Sp) motif on many proteins, RSX1,2SpXP. The two isoforms that interact with Raf-1 are phosphorylated in vivo on Ser185 in a consensus sequence motif for proline-directed kinases. The crystal structure of 14-3-3 indicates that this phosphorylation could regulate interaction of 14-3-3 with its target proteins. We have now identified a number of additional phosphorylation sites on distinct mammalian and yeast isoforms.